The king of the birds - Macam, Acree Graham (Groundwood Books / House of Anansi Press, 2016)
"Young Flannery collects birds of every type she can find. But when she brings home a peacock to be the king of her collection, he refuses to show off his colourful tail"--Front jacket flap.